2019
DOI: 10.1026/0932-4089/a000282
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a German Version of the Dimensions of the Learning Organization Questionnaire (DLOQ) in German Craft Companies

Abstract: Abstract. An explicit learning culture can help to systematize learning in small companies with a high degree of informal human resource development. The Dimensions of the Learning Organization Questionnaire (DLOQ; Marsick & Watkins, 2003 ) has already been used to assess learning culture in many international studies mainly with large organizations. However, the multidimensional structure of the DLOQ was criticized in the past. Therefore, this study (N = 856) investigated the dimensionality of a German tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…This assumption was supported by a recent study which was conducted in small companies and that showed that a continuous learning culture (i.e. a learning culture that is characterized by helping each other, being supported and being rewarded for learning) was positively connected to employees’ commitment (Kortsch and Kauffeld, 2019). In contrast, in large companies the learning culture was not important for employees’ turnover intentions (Egan et al , 2004).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…This assumption was supported by a recent study which was conducted in small companies and that showed that a continuous learning culture (i.e. a learning culture that is characterized by helping each other, being supported and being rewarded for learning) was positively connected to employees’ commitment (Kortsch and Kauffeld, 2019). In contrast, in large companies the learning culture was not important for employees’ turnover intentions (Egan et al , 2004).…”
mentioning
confidence: 83%
“…Faced with these changes, large organizations have spent much money on formal training and development (Blume et al , 2010) and research has focused on formal learning (Noe et al , 2014) as well as its supportive conditions (Holton et al , 2000; Massenberg et al , 2017). However, many studies have demonstrated that most of today’s learning in organizations happens informally (Cerasoli et al , 2018) – especially in organizations with low formal human resource development (HRD) which is mostly linked to one single person without any HR background (Kortsch and Kauffeld, 2019), such as small companies (Rowden, 2002). Thus, informal learning is becoming seemingly more crucial for organizational success.…”
mentioning
confidence: 99%
“…Although these studies have reported positive relationships between the learning organization and organizational outcomes, DLOQ research has not presented a clear understanding of specific relationships or influences associated with the proposed dimensions. Related, comprehensive comparative analyses of the results of DLQO studies have rarely been conducted to determine the appropriate level of analysis (Kim et al, 2015;Kortsch & Kauffeld, 2019). For instance, Song et al (2013) suggested that dialogue and inquiry, team learning, empowerment, and strategic leadership in the DLOQ should be organizational learning process factors while continuous learning, system connection, and embedded systems should be contextual factors.…”
Section: The Relationship Between Learning Organization and Organizational Performancementioning
confidence: 99%
“…This study has several implications for HRD practitioners. Many DLOQ studies have attempted to assess the learning culture within large organizations where active and continuous learning and sharing of learning are recognized as essential for organizational success (Kortsch & Kauffeld, 2019;Xie, 2019;Yoo, 2012). By understanding the features of the learning organization using the DLOQ, HRD practitioners can gain a holistic understanding of the cultural and structural elements at the individual, team, and organizational levels and can provide guidance on how organizations should perform (Watkins & Dirani, 2013).…”
Section: Implications For Practicementioning
confidence: 99%
“…Das Zusammenspiel aus formellem und informellem Lernen kann dabei als agiles Lernkontinuum beschrieben werden. Nach einem formellen Lernprozess folgt ein vom Lerner selbst initiierter informeller Lernprozess (Lernen von und mit Anderen durch informellen Austausch, Selbstversuch oder Selbststudium Kortsch und Kauffeld 2019 ; Kortsch et al. 2019 ; Decius et al.…”
unclassified